Proceedings of the 21st Conference on Computational Natural Language Learning (CoNLL 2017) 2017
DOI: 10.18653/v1/k17-1012
|View full text |Cite
|
Sign up to set email alerts
|

Embedding Words and Senses Together via Joint Knowledge-Enhanced Training

Abstract: Word embeddings are widely used in Natural Language Processing, mainly due to their success in capturing semantic information from massive corpora. However, their creation process does not allow the different meanings of a word to be automatically separated, as it conflates them into a single vector. We address this issue by proposing a new model which learns word and sense embeddings jointly. Our model exploits large corpora and knowledge from semantic networks in order to produce a unified vector space of wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(96 citation statements)
references
References 57 publications
1
94
1
Order By: Relevance
“…However, authors in [9] have shown that traditional word embeddings are not able to cope with the polysemy problem. Recently, some work [3,14] have tackled this issue. Cheng et al [3] propose to extend the skip-gram model [15] to identify the relevant word-concept pairwise given a context by jointly training the corresponding embeddings.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, authors in [9] have shown that traditional word embeddings are not able to cope with the polysemy problem. Recently, some work [3,14] have tackled this issue. Cheng et al [3] propose to extend the skip-gram model [15] to identify the relevant word-concept pairwise given a context by jointly training the corresponding embeddings.…”
Section: Introductionmentioning
confidence: 99%
“…The connection between words and concepts is set up based on either implicit senses (corpus-based) or explicit senses (inventoried in a knowledge resource). In the same spirit, Mancini et al [14] focus on the separate representation of each word sense according to only discrete senses provided by a semantic network (WordNet). A unified extended neural CBOW architecture allows building a shared vector space of both words and senses.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we also use a word overlap based approach (Lesk, 1986) for comparison. Finally, as we are actually testing the word and synset inter-connectivity in a shared vector space, we also include results from a similar experiment from (Mancini et al, 2016), and denote them as SW2V (Mancini et al, 2016) and AutoExtend (Rothe and Schütze, 2015). Apart from the four Synset2Vec models, we also use a combination of WSD3, M4, and a back-off strategy (Camacho-Collados et al, 2016) (M4+WNFS) for comparing to SW2V, since such strategy is also included.…”
Section: Discussionmentioning
confidence: 99%
“…These WSD systems are not dependent on general sense or word representation, but only rely on similarity metrics and underlying semantic resources. Recent works have tried to learn distinct representations for individual word senses based on clustering approaches (Reisinger and Mooney, 2010;Huang et al, 2012), mixed or hybrid sense and word embedding (Chen et al, 2014;Iacobacci et al, 2015), new embedding architectures (Mancini et al, 2016) and various knowledge sources (Rothe and Schütze, 2015). Embedding-based sense and word representation models have shown promising performance in WSD tasks , and they have better general-ization power of the vector representation of words, compared to similarity-based approaches.…”
Section: Word Sense Disambiguationmentioning
confidence: 99%
See 1 more Smart Citation